Experimental investigation of Fe-clay/organic interactions under asteroidal conditions. (1st February 2022) - Viennet, J.-C.; Le Guillou, C.; Remusat, L.; Baron, F.; Delbes, L.; Blanchenet, A.M.; Laurent, B.; Criouet, I.; Bernard, S.
Abstract: Carbonaceous chondrites contain both soluble and insoluble organic materials (SOM and IOM) which may have been produced in different environments via different processes or share possible genetic relationships. The SOM may have been produced from IOM during hydrothermal episodes on asteroids, and vice versa. The potential role played by the mineral matrix during these episodes (clay minerals of variable crystallinity) remains to be constrained. Here, we exposed a mixture of formaldehyde and glycolaldehyde with ammonia-bearing liquid water together with Fe-rich smectitic minerals to hydrothermal conditions mimicking asteroidal conditions. We used both amorphous gel of smectite or crystalline smectites in order to understand the influence of the crystallinity on the evolution of OM. The organo-mineral experimental residues were characterized at a multiple length scales using X-ray diffraction and microscopy/spectroscopic tools. Results evidence that some IOM polymerizes/condenses in the absence of Fe-rich smectites. Yet, the presence of Fe-rich smectites inhibits this production of IOM. Indeed, the interactions between the SOM and clay surfaces (interlayers or edges) reduce the concentration of SOM available for polymerization/condensation reactions, a necessary step for the production of IOM. In addition, the presence of OM disorganizes the crystallization of the Fe-rich amorphous silicates, leading to smaller crystal sized particles exhibiting a lower permanent charge. This might suggests that the smectite permanent charge distribution may help better constraining the origin and evolution of chondritic clay minerals. Altogether, the present study sheds new light on the organo-mineral interactions having occurred during hydrothermal episodes onto/within chondritic asteroids. Indeed, IOM formation from OM-rich aqueous fluids does not occur during the alteration of amorphous silicates. This would mean that IOM is either produced within pockets free of clay minerals or initially accreted as IOM-rich grain. Last, about ∼50 wt% of the initial C could not be removed from the clay minerals at the end of the experiments using classical solvent extraction protocols, demonstrating that a high fraction of the SOM in carbonaceous chondrites may have been overlooked.